De novo design of D-peptide ligands: Application to influenza virus hemagglutinin - Jarek Juraszek; Rameshwar U. Kadam; Davide Branduardi; Jeroen van Ameijde; Divita Garg; Nicolas Dailly; Mandy Jongeneelen; Jan Vermond; Just P. J. Brakenhoff; Boerries Brandenburg; Maria J. P. van Dongen; Ronald Vogels; et al. (Proceedings of the National Academy of Sciences, 2025)
D-peptides hold great promise as therapeutics by alleviating the challenges of metabolic stability and immunogenicity in L-peptides. However, current D-peptide discovery methods are severely limited by specific size, structure, and the chemical synthesizability of their protein targets. Here, we describe a computational method for de novo design of D-peptides that bind to an epitope of interest on the target protein using Rosetta’s hotspot-centric approach. The approach comprises identifying hotspot sidechains in a functional protein–protein interaction and grafting these side chains onto much smaller structured peptide scaffolds of opposite chirality. The approach enables more facile design of D-peptides and its applicability is demonstrated by design of D-peptidic binders of influenza A virus hemagglutinin, resulting in identification of multiple D-peptide lead series. The X-ray structure of one of the leads at 2.38 Å resolution verifies the validity of the approach. This method should be generally applicable to targets with detailed structural information, independent of molecular size, and accelerate development of stable, peptide-based therapeutics.